The role of humoral immune responses in determining susceptibility of A/J and C57BL/6 mice to infection with Trypanosoma congolense - Morrison, W. Ivan; Murray, M. (Wiley, 1985)
Summary The relative resistance of C57BL/6 mice to infection with Trypanosoma congolense as compared to A/J mice was found to be independent of the infective dose of trypanosomes and required an intact immune system, as sublethal levels of gamma irradiation abolished the differences in susceptibility between the two strains. C57BL/6 mice produced earlier and quantitatively superior antibody responses both to the variable surface glycoprotein and to common membrane antigens on the trypanosome than A/J mice. No difference was observed in the class of antibody produced. In parallel with the specific response, C57BL/6 mice also generated higher levels of antibody to an unrelated antigen (TNP) and developed higher levels of total serum IgM. However, despite the low levels of both specific antibody and antibody to TNP in A/J mice, these animals developed massive increases in total serum IgG2a. The role of this selective activation of IgG2a producing cells in the susceptibility of the A/J mice was unclear. Although susceptibility was closely correlated with specific antibody responses during infection, the two strains of mice showed a similar capacity to respond to fixed doses of irradiated trypanosomes. This indicates that an inherent difference in immune responsiveness to the trypanosomal antigens is not the major factor determining susceptibility. Moreover, the finding that a proportion of A/J mice which received infective and irradiated trypanosomes simultaneously showed depressed antibody responses to the trypanosome, suggests that active infection of A/J mice with T. congolense impairs their ability to initiate an appropriate immune response to the trypanosome.